Mechanisms for blood pressure reduction following isometric exercise training: a systematic review and meta-analysis. Issue 11 (8th November 2022) - Edwards, Jamie J.; Wiles, Jonathan; O'Driscoll, Jamie
Abstract : Objective: Isometric exercise training (IET) is established as an effective antihypertensive intervention. Despite this, the physiological mechanisms driving blood pressure (BP) reductions following IET are not well understood. Therefore, we aimed to perform the first meta-analysis of the mechanistic changes measured following IET. Methods: PubMed, Cochrane library and SPORTDiscus were systematically searched for randomized controlled trials published between January 2000 and December 2021 reporting the effects of IET on resting BP and at least one secondary mechanistic parameter following a short-term intervention (2–12 weeks). Results: Eighteen studies with a pooled sample size of 628 participants were included in the final analysis. IET produced significant reductions in resting systolic and diastolic BP of 9.35 mmHg (95% confidence interval [CI] = −7.80 to −10.89, P  < 0.001) and 4.30 mmHg (CI = −3.01 to −5.60, P  < 0.001), respectively. Mechanistically, IET produced a statistically significant reduction in resting heart rate (mean difference [MD]: −1.55 bpm, CI = −0.14 to −2.96, P  = 0.031) and a significant increase in stroke volume (MD: 6.35 ml, CI = 0.35 to 12.60, P  = 0.038), with no significant change in cardiac output. Conversely, total peripheral resistance (TPR) significantly decreased following IET (MD: −100.38 dyne s −1 cm 5, CI = −14.16 to −186.61, P  = 0.023), with significant improvements in the low frequency to high frequency heart rate variability ratio (MD: −0.41, CI = −0.09 to −0.73, P  = 0.013) and baroreceptor reflex sensitivity (MD: 7.43 ms/mmHg, P  < 0.001). Conclusion: This work demonstrates that a reduction in TPR, potentially mediated through enhanced autonomic vasomotor control, is primarily responsible for BP reductions following IET. Furthermore, this novel analysis suggests wall squat interventions to be the most effective IET mode, with clinically relevant differences in BP reductions compared to handgrip and leg extension IET; although future direct comparative research is required.